GEANT4 simulation of neutron transport and scattering in media - Deiev, O.S. (Вопросы атомной науки и техники, 2013)
GEANT 4 simulation toolkit and PhysList QGSP BIC HP for simulate neutron transport and scattering was used. Primary neutron spectrum was modeled similar spectrum of ²³⁹Pu - Be(α, n) neutron source. Spectra of neutron passing through the material and scattered were obtained. Number of thermal neutrons after passing various materials were calculated. Detector-dosimeter MKS-01R was used for measurements of the experimental thermal neutron flux from ²³⁹Pu - Be(α, n) neutron source. Satisfactory agreement between calculations and experiment was obtained. Розрахунковий код GEANT4 i фiзичний лист QGSP BIC HP використовувались для моделювання транспорту i розсiяння нейтронiв. Отриманi спектри нейтронiв, що проходять через шари матерiалу i розсiяних назад. Первинний спектр нейтронiв моделюється як у джерела ²³⁹Pu−Be(α, n). Розрахованi кiлькостi теплових нейтронiв пiсля проходження рiзних матерiалiв. Для експериментального вимiрювання теплового потоку нейтронiв використаний детектор-дозиметр МКС-01Р. Згода мiж розрахунками i експериментом задовiльна. Расчетный код GEANT4 и физический лист QGSP BIC HP использовались для моделирования транспорта и рассеяния нейтронов. Получены спектры нейтронов, проходящих через слои материала и отраженных назад. Первичный спектр нейтронов моделируется как у источника ²³⁹Pu − Be(α, n). Рассчитаны количества тепловых нейтронов после прохождения различных материалов. Для экспериментального измерения теплового потока нейтронов использован детектор-дозиметр МКС-01Р. Согласие между расчетами и экспериментом удовлетворительное.